Proyecto de factibilidad para la implementación de una empresa de lavado automático de vehículos livianos en la ciudad de Puerto Francisco de Orellana, para el año 2015. - Salavarria Loor, Edwin Byron (2016)
In the city of Francisco one of the particular phenomena which is evident in the sector is that while it is true there is a lot of vehicles there are no dealers, much less companies offering vehicle services, two gas stations that are in the city they are the only ones providing review service stations and washing vehicles by most of the population with this transport has to move to nearby provinces or alternate for the respective vehicle maintenance. As a significant growth of the fleet in the industry, establishing a company car wash meant the opening of new jobs and employment opportunities for city dwellers. This research work aims to determine the feasibility of creating a company automatic washing of light vehicles in the city of Puerto Francisco de Orellana, Orellana Province, 2015, for which the application of different methods are required and Techniques, regarding the methods used, deductive, inductive, and Statistical. The use of them allowed to meet the objectives, and follow in the footsteps of understanding and demonstration of the same application. In the market study in the canton Francisco de Orellana, with a sample of 383 families and 2 companies that offer the service vehicle wash; has determined the potential demand for 8,950 families, Demand Real 6,534 families, Effective. Demand 6,338 families, which used 190,140 services vehicular washing, the supply of 6,760 services and unmet demand of 183,380 services, which allowed us to determine that the project you can and should be run by the results obtained in the analysis of demand, supply and marketing levels this service. The installed capacity of the project determines that the company will be able to provide 17,520 services and whose capacity utilization will be 15,768 service automatic washing for light vehicles, and the location of it to be located in the town of Francisco de Orellana is determined, in the streets on October 9 and Rio Napo. The production process requires the use of suitable equipment, which will guarantee for quality service and moderate prices. Likewise an administrative study determined as a Limited Liability Company, and functional organizational structure to both legislative hierarchical levels, Executive, Consultant Level, held Assistant Support, Operational Level, as well as operating manuals. The project reaches an investment of $ 190,957.69 and will be financed with a contribution from the partners 48% of the total investment and a loan that will keep the project with the National Finance Corporation will constitute 52%. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 4,857.66, for this project IRR is 15.64%, the time required to recover the original investment would be 5 years and 7 days, the sensitivity values are less than one, therefore do not affect the project changes in costs and revenues increased 11.6% and decreased in 10.4%, respectively, ie the project is not sensitive to these changes. Subsequently the conclusions and recommendations of the most significant project is proposed.